SCHEME OF GOOD TAXPAYERS: LYRICAL PROPOSAL; UNACHIEVABLE ASPIRATION - Castro Contreras, Teodoro (2012)
The legal discipline called Finance and Tax Law is constituted by a conceptual system, equipped with a dogmatic immanence that allows describe it like a closed one, cultivated by a community of specialist relatively well defined. The Tax discipline has been helped by the conception of the rule of law, which has permitted to identify the strengthening of the trend to the legal immanence. It is inconceivable a society which not consider the tax institution. If it did, would cease to be a political society that actually exists. The tax dialectic could also be formulated within the understanding that presupposed by the private property, because only can pay the taxation, the subject of the taxable event, but at the same time, puts into question the core of private property, through which exists the institution of the tribute. In this brief investigation, we explain the shortcomings of the standard relating to the benefits that the legislature intended to give taxpayers, when it comes to including them in a Scheme of Good Taxpayers, letting the tax collector bring the guidelines and become in judge and jury in a process that was thought would favor the taxpayer.